ANALISIS PENGARUH PERTUMBUHAN EKONOMI, INFLASI, SUKU BUNGA DAN HARGA MINYAK DUNIA TERHADAP INDEKS HARGA SAHAM GABUNGAN DI INDONESIA PERIODE TAHUN 2001-2017 - Mahendra, A. (Jurnal Manajemen dan Bisnis, 2020)
This research is intended to know the influence of economic growth, inflation, interest rate and world oil prices variables to join stock price variable in Indonesia. Population in this research is Indonesia and 68 of them were selected to be the samples for this research through purposive sampling technique. Estimates conducted by the multiple regression analysis. The data that were used in this study were secondary data, consisted of Economic Growth, Inflation, Interest Rate and World Oil Prices to joint stock price index for the year 2001-2017. The results of this research, that Based on the partial test (t test), the Inflation variable has no significant effect while the Economic Growth, Interest Rateand World Oil Prices variables have a significant effect on the variables of the Joint Stock Price Index in Indonesia. But the simultan test (F test), economic growth, inflation, interest rate and world oil prices have a significant effect on the variables of the joint stock price index.